Keynotes: Asia in Malaysia Forum - Khoo, Kay Kim (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
The phrase "Asia in Malaysia Forum" raises many eyebrows. Size-wise and population wise, Malaysia is a midget. It seems incongruous that one should speak of "Asia in Malaysia". The phrase of course could be interpreted to mean "the study of Asia n Malaysia". Intention-wise, that is true. But it is more than that. It expresses a situation which Malaysians themselves are not very aware of, that is, that Malaysia can be deemed to be ’Asia in miniature’ or as the Ministry of Culture, Arts and Tourism puts it: "Malaysia Truly Asia" for the simple reason that so much of the religious and cultural components of numerous parts of the Asian continent are found here.